2014
DOI: 10.1152/ajpregu.00502.2013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic binge alcohol consumption alters myogenic gene expression and reduces in vitro myogenic differentiation potential of myoblasts from rhesus macaques

Abstract: Chronic alcohol abuse is associated with skeletal muscle myopathy. Previously, we demonstrated that chronic binge alcohol (CBA) consumption by rhesus macaques accentuates skeletal muscle wasting at end-stage of simian immunodeficiency virus (SIV) infection. A proinflammatory, prooxidative milieu and enhanced ubiquitin proteasome activity were identified as possible mechanisms leading to loss of skeletal muscle. The possibility that impaired regenerative capacity, as reflected by the ability of myoblasts derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 43 publications
5
38
0
Order By: Relevance
“…Moreover, they show a marked decrease in skeletal muscle mass (SAIDS wasting) and dysfunctional skeletal muscle phenotype, which we found were associated with accelerated time to end-stage disease, relative to isocaloric sucrose SIV-infected animals (Molina et al 2006). Our findings indicate that the mechanisms underlying (and preceding) accentuated SAIDS wasting include the amplification of localized skeletal muscle inflammation, profound depletion of skeletal muscle anti-oxidant capacity (oxidative stress), increased proteasomal activity, and decreased myoblast differentiation potential (LeCapitaine et al 2011; Simon et al 2014). …”
Section: Introductionmentioning
confidence: 83%
“…Moreover, they show a marked decrease in skeletal muscle mass (SAIDS wasting) and dysfunctional skeletal muscle phenotype, which we found were associated with accelerated time to end-stage disease, relative to isocaloric sucrose SIV-infected animals (Molina et al 2006). Our findings indicate that the mechanisms underlying (and preceding) accentuated SAIDS wasting include the amplification of localized skeletal muscle inflammation, profound depletion of skeletal muscle anti-oxidant capacity (oxidative stress), increased proteasomal activity, and decreased myoblast differentiation potential (LeCapitaine et al 2011; Simon et al 2014). …”
Section: Introductionmentioning
confidence: 83%
“…The pro-inflammatory milieu present in the SKM of the CBA-SIV animals potentially contributes to the up-regulation of pro-fibrotic gene expression and favors collagen expression, which we predict is likely to impair satellite cell (resident SKM stem cells) function and muscle regeneration. Recent studies from our laboratory have demonstrated that myogenic gene expression is markedly altered in satellite cells isolated from CBA animals and this is associated with impaired myotube formation (Simon et al, 2014). In addition, the down-regulation of genes that code for proteins involved in anabolic signaling suggests that the overall loss in SKM is likely the result of combined enhancement of proteolysis and suppression of anabolic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating myoblasts can be fixed, stained, and visualized, and indices of differentiation can be quantified. Using the protocols described herein, we have previously found that myoblasts isolated from simian immunodeficiency virus–infected male rhesus macaques subjected to chronic binge alcohol administration have reduced myoblast differentiation potential compared to those who were not administered alcohol (Simon et al., ; Simon, Ford, et al., ). The use of these protocols to assess differentiation provide support for hypothesized mechanisms underlying alcoholic myopathy (Molina, Simon, Amedee, Welsh, & Ferguson, ; Simon, Jolley, & Molina, ).…”
Section: Commentarymentioning
confidence: 97%
“…Growth and repair of skeletal muscle tissue requires satellite cells to be activated, proliferated, differentiated, and fused with existing muscle fibers in a process termed myogenesis (Yin, Price, & Rudnicki, ). Some stimuli, such as resistance or high‐force exercise and anabolic hormones, promote myogenesis (Bellamy et al., ; Goh et al., ; Sinha‐Hikim, Cornford, Gaytan, Lee, & Bhasin, ), whereas stimuli such as alcohol and catabolic hormones impair myogenesis (Dong, Pan, & Zhang, ; McCroskery, Thomas, Maxwell, Sharma, & Kambadur, ; Simon et al., ; Simon, Ford, et al., ). Myogenesis can be studied in vitro using myoblasts isolated from skeletal muscle cultured first in high‐serum medium to promote myoblast proliferation and then in low‐serum medium to promote differentiation and fusion.…”
Section: Introductionmentioning
confidence: 99%